LEGAL ANALYSIS OF THE EFFECTIVENESS OF THE AUTOGATE SYSTEM IN FACILITATING THE TRAFFIC OF FOREIGNERS AT INTERNATIONAL PORTS (RESEARCH STUDY IN BATAM CITY) - Lazuardi Farisco; Siti Nurkhotijah; Sayid Fadhil; Erniyanti (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The international port in Batam City serves as the main entry point for the flow of foreigners, playing a strategic role in tourism, business, and cross-border activities. To improve the efficiency of immigration checks and reduce manual queues, the government has implemented the autogate system, an automated inspection system based on biometric technology. However, the implementation of this system still faces various challenges from technical, legal, and social aspects, such as system disruptions, regulatory gaps, and low user understanding. This study aims to analyze the legal regulations of the autogate system, evaluate the effectiveness of its implementation, and identify obstacles and possible solutions to facilitate the movement of foreigners at the international port of Batam City. This study uses a normative juridical and empirical juridical approach, with secondary data collected through document studies and primary data gathered through interviews and direct observation at Batam Center, Sekupang, and Harbour Bay ports. The analysis is conducted based on the framework of Modern Law Theory (Eugen Ehrlich), Legal System Theory (Lawrence M. Friedman), and Legal Certainty Theory (Sudikno Mertokusumo). The research results indicate that the autogate system already has a legal basis through the Immigration Law, Minister of Law and Human Rights Regulations, as well as regulations on personal data protection. However, its implementation has not been optimal due to weak infrastructure readiness, lack of staff training, and uneven public understanding. Therefore, it is necessary to strengthen technical policies, enhance technology and human resource capacity, and conduct ongoing public outreach to improve the effectiveness and legal certainty in the use of the autogate system.